Validating nutrient selection for product-group-specific nutrient indices for use as functional units in life cycle assessment of foods - Kårlund, Anna; Kyttä, Venla; Pellinen, Tiina; Tuomisto, Hanna. L.; Pajari, Anne-Maria; Kolehmainen, Marjukka; Saarinen, Merja (Cambridge University Press, 2025)
The ability to provide adequate nutrition is considered a key factor in evaluating the sustainability of foods and diets. Nutrient indices are used as functional units (FUs) in life cycle assessment of foods to include nutritional performance in the environmental assessment of a product. Several general and food group-specific nutrient indices exist but many lack validation, particularly when used as FU. In addition, the nutrient selection strategies and reference units for nutrient intake can vary considerably among studies. To validate intake-based product-group-specific nutrient indices previously developed for protein (NR-FIprot) and carbohydrate (NR-FIcarb) foods and for fruits and vegetables (NR-FIveg), we applied principal component analysis to investigate correlations between nutrients in foods and dishes representing a typical Finnish diet. The reference amounts for meal components were based on a plate model that reflected Finnish dietary recommendations. The portion sizes for the different food groups were anchored at 100 g, 135 g and 350 g for proteins, carbohydrates and fruits/vegetables, respectively. Statistical modelling largely validated the NR-FI indices, highlighting protein foods as sources of niacin, vitamin B12 and selenium, carbohydrate foods as sources of magnesium, iron and phosphorous, and fruits/vegetables as sources of potassium, vitamin K, vitamin C, fibre and thiamine. However, in contrast to the intake-based approach applied in NR-FIprot, the dietary recommendation-based validation process suggested that fruits and vegetables should be favoured as sources of riboflavin and vitamin B6.